Aerodynamic Configuration Optimization of a Propeller Using Reynolds-Averaged Navier–Stokes and Adjoint Method - Yang Zhang; Yifan Fu; Peng Wang; Min Chang (Energies, 2022)
The discrete adjoint method was used to optimize the aerodynamic configuration in order to increase the efficiency and precision of design. The fully unstable simulation of propeller rotation was avoided using the quasi approach. In the meantime, the gradient-based optimization approach was extended to the rotating coordinate in which the propeller blades were running, thereby increasing the dimension of the shape parameters as multi-coordinates were taken into account. However, the precision of the propeller optimization was improved by expanding the range of variation for design parameters. Using the current design framework, the propeller’s torsion angle, blade chord length, and blade profile were modified independently by an optimization solver, resulting in a notable acceleration.